Differences in students critical thinking skills and interest with guided inquiry and learning videos - Fianicha Shalihah; H. Harlita; Alanindra Saputra (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
This study aimed to determine the differences: (1) critical thinking skills, (2) interest in learning, and (3) critical thinking skills and learning interests of class XI students using the guided inquiry learning model accompanied by learning videos. The method used is a quasi experiment with a posttest only control group design. The population in this study was class XI MIPA with 289 students and the sample used was class XI 4 and class XI 5 with 84 students. The sampling technique used is cluster random sampling. Collecting data on critical thinking skills uses a test, while collecting data on interest in learning uses a questionnaire. The data analysis technique used the t test and the manova test. The results showed that H1 (t test) obtained the value of Sig. = 0.041 (<0.050), H2 (t test) obtained Sig. = 0.041 (<0.050), and H3 (manova test) obtained Sig. = 0.007 (<0.050). It was concluded that there were significant differences: (1) critical thinking skills, (2) interest in learning, and (3) critical thinking skills and learning interests of class XI students using the guided inquiry learning model accompanied by learning videos.